Banking Strategy COmpetitive Landscape for China Banking Industry - Lee Koon, Teo (2010)
China is one of the most exciting countries for global bankers, the large population and strong economic growth signify amber of business opportunities, but more importantly, it’s increasingly influence on the world economy means no one can neglect the market potential. Given its huge market potential, global bankers, have been constantly seeking market entry and development opportunities in the China’s banking sector.